Race in the Shipbuilding Industry: Cases of South Korea, Japan and China - Tan, Soo Kee (WILAYAH: The International Journal of East Asian Studies, 2017)
The shipbuilding industry is enormously important to the South Korean economy. It serves as the backbone of survivals of many other industries in Korea. The success story of the Korean shipbuilding industry is the national pride for the Korean people because it started from scratch in the 1970s and reached the world number one position in just three decades. Top Korean shipbuilders such as Hyundai Heavy Industries, Daewoo Shipbuilding and Marine Engineering and Samsung Heavy Industries have taken the top three ranking positions in the world as the finest and largest global shipbuilders. In the early 2000s, Korean shipbuilders were dominant enough to command nearly 40 percent of the global production in shipbuilding. Nonetheless, the situation has changed with the emergence of new competitors in the market. Chinese shipbuilders and the revived Japanese shipbuilders are now strong contenders in the industry and a threat to the Korean shipbuilders. Since 2014, the global shipping market has been hit hard with the sudden drop in crude oil price, and this change in demand tremendously affected the Korean shipbuilding industry. The Korean shipbuilding industry nearly collapsed in 2016, which prompted huge interventions from the Korean government. The unexpected changes within the shipbuilding industry shocked the Koreans. This article has two objectives. First, it aims to study what caused the sudden shift in the Korean shipbuilding industry. Second, to what extent have the Chinese and Japanese shipbuilders affected the Korean shipbuilders, and what is their current status in the global market? Ultimately, the article looks at the future faced by Korean shipbuilders due to the competition from China and Japan.